RASIO PENGELOLAAN DANA PIHAK KETIGA TERHADAP TOTAL KREDIT PADA PT. BANK MANDIRI (PERSERO) Tbk - Hayanuddin Safri; Pristiyono Pristiyono (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2020)
Management of Third Party Funds at PT Bank Mandiri (Persero) Tbk for the period 2013-2017 shows an increasing trend. For 2013, DPK amounted to Rp. 508,996,256,000,000, - with a total credit of Rp. 467,170,449,000,000, with a fairly healthy predicate value. For 2014 DPK amounted to Rp. 583,448,915,000,000, -with a total credit of Rp. 523,101,917,000,000, with a predicate value that is quite healthy. For 2015, DPK amounted to Rp. 622,332,331,000,000, with a total credit of Rp. 586,675,437,000,000, with a predicate value that was quite healthy. For 2016, DPK was IDR 702,060,230,000,000, with a total credit of IDR 649,322,953,000,000, with a fairly healthy predicate value and for 2017 DPK was IDR 749,583,982,000,000, - with a total credit of IDR 712,037,865,000,000 , with a predicate value that is quite healthy.